Green space and subjective well-being in the Just City: A scoping review. Issue 120 (June 2021) - Sharifi, Farahnaz; Levin, Iris; M.Stone, Wendy; Nygaard, Andi
Highlights: Equity needs to be paramount in the relationship between green space and well-being. There is heterogeneity in the effects of green space. There are unintended adverse consequences of green space in the form of gentrification. Vertical distance and subjective accessibility are underdeveloped areas. Quality of green space needs to be matched with needs of disadvantaged communities. Abstract: Rapid urban change, in the form of green space (GS) degradation, is exacerbating inequalities in cities, which in turn may aggravate health and subjective well-being (SWB) disparities. Despite extensive evidence-based literature, gaps remain in our understanding of the relationship between GS and SWB in the Just City context—a concept that seeks achieving equity for the residents as its major objective. We conducted a scoping review and a thematic analysis by searching in four academic databases. GS, SWB and Just City were searched together, drawing from recent literature and identifying 52 studies that met the inclusion criteria, from 1481 search results. Three themes were identified in the analysis, with under-developed areas documented in each. These themes include 'quantifying GS accessibility', 'heterogeneity in the effect of GS', and 'vulnerable communities' needs and diverse populations' aspirations'. Research gaps, including ambiguity around causes of inequality, a lack of monitoring changes, inconsistency in GS measurement, subjective access, and vertical distance neglection, were identified in the literature. Given the considerable focus on distribution of GS, the literature frequently neglects social justice dimensions. This arises from the need to consider justice beyond the distribution of GS. Findings also highlight the role of context-sensitive planning. Specifically, it is suggested that to achieve Just City ideals, in operational terms, there is a need to improve vulnerable communities' capability with using GS, aiming to promote their SWB and attenuate inequalities.